The Effect of Macroeconomic Factors on the Detection Value of the Firm: An Application in Istanbul Stock Exchange - Ulusoy, Tolga; Ugur, Sevil Oguz (International Journal of Economics, Business and Management Studies, 2020)
The aim of this study is to examine the effect of macroeconomic factors on firm value determination. First, macroeconomic factors such as national income, inflation, interest rate, money supply, exchange rate, employment level and oil price effects on firm’s stock prices have been researched a firm traded on the Istanbul Stock Exchange is selected and wtih the data including the period 2006: 01 - 2016: 06 by simple correlation and multiple regression analysis. Secondly, firm values is determined according to years by using the Price / Earning Ratio method which is one of Market Value Approach in the company valuation methods. Market Value Approach due to the price comparison creating opportunities for firms in exchange methods, this approach provides a comparison of companies in industry or the same sector arm. For the investors, the price / profit ratio method is preferred because the data can be easily analyzed and the results can be obtained in a shorter time. As a result of the study, it is concluded that the firm's stock prices are positively correlated with national income, exchange rate, money supply and employment, while there is a negative correlation between inflation, interest rate and oil prices. While the firm's balance and income statement data and past financial statements are helpful in valuation, it is also possible to estimate the firm’s value of the next year, so the firm’s value method needs to be selected well.